Bioactivity Analysis of Chalcone-Derived Compounds Based on In-Silico Molecular Docking Study - Sarie, Aldila Divana; Utami, Marsah Rahmawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Chalcone compounds are aromatic ketones and enones that have been found to have several activities, such as antimalarial, antioxidant, anti-inflammatory, anticancer, antiviral, anti-HIV, antifungal, antihyperglycemic, and carboxygenase inhibitors. A ligand's bioactivity can be predicted through in-silico tests using molecular docking. Molecular docking studies are conducted to study the interaction between ligand and receptor and identify the receptor's active site that matches the ligand when the ligand and receptor bind in a stable complex. This study can be a preliminary test before conducting in vitro and in vivo tests. This narrative review aims to analyze information on the bioactivity of chalcone-derived compounds and their derivatives through an in silico molecular docking approach in the form of binding affinity values and amino acid residues that bind. The method used is a literature study of 13 research articles found through the Semantic Scholar and Springer Link databases. The review results showed that the new compounds derived from chalcone compounds have a good range of bioactivity, as seen from the binding affinity values, which show lower values when compared to other test ligands and referenced ligands. The functional groups that have an important role in the interaction between ligands and proteins between ligands and receptors are triazole, methoxy, amine, halogen, carbonyl, hydroxyl, and thiol groups bound to the reactive structure of the α,β unsaturated ketone aromatic ring in the structure of the chalcone compound. The compounds that show promising activity can be further investigated as new drug candidates.